Design and construction of a co-planar power bus interconnect for low inductance switching - Lin, Xi; Li, Jianfeng; Johnson, Mark (2017)
A co-planar tab-slot type of interconnect demonstrator for connecting power switching devices and DC bus capacitors has been designed and constructed, aimed at low inductance switching. The demonstrator is composed of a double-sided tab connector and a dual polarity slot. This type of interconnect eliminates the use of screw terminal connection between a power module and the DC bus as well as between the DC bus and power capacitors, thus serves to maintain a coplanar current profile throughout the power distribution path. Parasitic analysis both in impedance testing and in Finite Element simulation suggests that the inductance in the bus loop of the demonstrator is approximately half of that achieved in an equally dimensioned busbar with conventional screw terminals.